2021
DOI: 10.4108/eai.23-6-2021.170241
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Agent-Based AODV Routing Protocol for MANET

Abstract: The mobile ad-hoc network (MANET) is a special mobile network that has self-configuration and self-establish abilities to communicate conveniently. MANET is forming mobile devices such as mobile phones, personal digital assistants (PDAs), laptops, etc. As a result of the rapid, flexibility, and facilitate in communication, nowadays, MANET has revolutionized many real-life applications, ranging from smart agriculture and smart cities to forest fire detection systems, and expected to have vital contributions int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Authors in literature presented an improved version of AODV, which is known as Agent-based AODV (A-AODV), which operates on three principles: routing metric, route discovery, and routing algorithm. Simulation results show that A-AODV always has better PDR compared to AODV and DSR ( Nguyen et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Authors in literature presented an improved version of AODV, which is known as Agent-based AODV (A-AODV), which operates on three principles: routing metric, route discovery, and routing algorithm. Simulation results show that A-AODV always has better PDR compared to AODV and DSR ( Nguyen et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…The simulation results have shown that the proposed routing scheme improved significantly packet congestion probability compared to existing AODV‐based routing schemes. Also according to this approach, 34 propose an advanced AODV scheme that improved from the traditional AODV scheme for MANETs architectures in the 5G context. This protocol leverages multi‐channel communication, it collects routing information based on mobile agents.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Besides data aggregation, data pressure is also a technique to diminish the size of data packets transmitted to the sink, thus also saving energy. Hau et al [20] introduced the improvement of the AODV routing protocol by using intelligent agents for efficient energy. Tan et al [21] proposed a sector tree based on a clustering routing protocol for efficient energy, in which the nodes in a cluster communicate with each other based on the minimum spanning tree connecting.…”
Section: Related Workmentioning
confidence: 99%